2003
DOI: 10.1095/biolreprod.102.009852
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic Competence of Equine Oocytes and Pronucleus Formation after Intracytoplasmic Sperm Injection (ICSI) as Related to Granulosa Cell Apoptosis1

Abstract: Follicle atresia and granulosa cell apoptosis may be related to oocyte meiotic and developmental competence. We analyzed the relationships among granulosa cell apoptosis, initial cumulus morphology, oocyte nuclear maturation in vitro, and pronucleus formation after intracytoplasmic sperm injection (ICSI) in the horse. For each follicle, the size was measured and granulosa cells were used for DNA laddering analysis. Oocytes were evaluated for cumulus morphology, cultured for in vitro maturation, and submitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 58 publications
3
50
0
Order By: Relevance
“…Interestingly, in the horse the recovered cumulus-oocyte complexes are a mixed population with either a compact or an expanded cumulus. While expanded cumulus -oocyte complexes are often discarded for in vitro embryo production in cattle and pigs, they represent about 40% (2060/5127, our observations) of the total population of recovered oocytes in the horse and seem to have some developmental competence for maturation (Dell'Aquila et al 2003), cleavage (Choi et al 2002) and blastocyst formation (Zhang et al 1989). Another peculiar aspect specifically relevant to horse nuclear transfer is the reported (Choi et al 2002, Li et al 2002 low ability of oocytes to fuse with donor cells and the limited developmental competence of nuclear transfer (NT)-embryos in vitro.…”
Section: Introductionmentioning
confidence: 68%
“…Interestingly, in the horse the recovered cumulus-oocyte complexes are a mixed population with either a compact or an expanded cumulus. While expanded cumulus -oocyte complexes are often discarded for in vitro embryo production in cattle and pigs, they represent about 40% (2060/5127, our observations) of the total population of recovered oocytes in the horse and seem to have some developmental competence for maturation (Dell'Aquila et al 2003), cleavage (Choi et al 2002) and blastocyst formation (Zhang et al 1989). Another peculiar aspect specifically relevant to horse nuclear transfer is the reported (Choi et al 2002, Li et al 2002 low ability of oocytes to fuse with donor cells and the limited developmental competence of nuclear transfer (NT)-embryos in vitro.…”
Section: Introductionmentioning
confidence: 68%
“…Ovaries from mares of unknown reproductive history, obtained at two local abattoirs located at a distance of 20 km (30 min) from the laboratory, were transported and processed as previously described (Dell'Aquila et al 2003). COCs were identified in the mural granulosa cells using a dissection microscope and only those complexes, classified as having Cp or Exp cumulus investment, were used (Dell'Aquila et al 2003). Oocytes for these studies (western-blot, IVM cultures, immunofluorescence before and after IVM, and MAPK 3/1 analysis) were used immediately and their further processing is detailed in related sections.…”
Section: Methodsmentioning
confidence: 99%
“…Among these, the horse has been previously used as a model to investigate oocyte physiology due to its particularly large follicle size, which allows the possibility to relate oocyte meiotic and developmental competence with biochemical and molecular features of corresponding follicle cells (Goudet et al 1997, Hinrichs & Schmidt 2000, Hinrichs et al 2005, Dell'Aquila et al 2003, 2004, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Horse oocytes with compact cumuli (Cp) are largely recovered from histologically viable follicles, whereas oocytes with expanded cumuli (Ex) are largely recovered from atretic follicles [49]. Ex oocytes originate more frequently from follicles with advanced apoptosis than Cp oocytes [50]. It has been reported that bovine oocytes with mildly atretic cumulus cells yield a higher blastocyst rate than oocytes without visibly signs of atresia [51].…”
Section: Discussionmentioning
confidence: 99%